Health Tourism Training: A Study on Secondary Education - Çalışkan, Serkan; Sevim, Burhan; Tuncer, Kurtuluş (International Journal of Health Management and Tourism, 2024)
Aim: In previous studies on health tourism education in Türkiye, it has been observed that it is the subject of higher education. As in many European countries, vocational education starts after primary education in Türkiye. This study aims to answer the questions of what is the place and importance of health tourism education at the vocational secondary education level in Türkiye and how this situation is related to Türkiye's health tourism policies and goals, such as becoming the capital of health tourism in 2053 and creating a global brand with the slogan "Health Turkiye". Methods: The research used a case study design as a qualitative research method. For the research, the documents and development plans of the curricula of 53 fields and 114 branches in vocational secondary education were examined. Results: In the examination, it was seen that there are courses related to health tourism in the 4-year education programs in the fields of health services and accommodation and travel services. However, it was observed that 50% of the courses in the curriculum of Accommodation and Travel Services and 100% in the curriculum of Health Services are elective courses. Conclusion: Because the place and importance of health tourism education at the secondary education level have not been examined before, and Turkiye's targets regarding health tourism, our study is a pioneering and important study in determining the status of health tourism in the framework curricula at the secondary education level
Keywords: Policy and Administration (Other); Turizm Politikası; Tourism Policy; Politika ve Yönetim (Diğer); Development Plan; Health Tourism; Vocational Training